Mechanism of LCN2 in cerebral ischemia-reperfusion injury - Cai, Luo-yang; Yuan, Ying; Huang, Hai; Zhang, Jin; Zou, Xin-yi; Zhang, Xiao-ming (Frontiers in Neuroscience, 2025)
Cerebral ischemia-reperfusion injury (CIRI) is a complex pathophysiological process faced by brain tissues after ischemic stroke treatment, which involves mechanisms of inflammatory response, oxidative stress and apoptosis, and severely affects treatment outcome. Lipocalin-2 (LCN2), an acute-phase protein, is significantly up-regulated after CIRI and promotes neural repair by enhancing astrocyte phagocytosis, but its over-activation may also trigger secondary inflammation and demyelination injury. LCN2 also plays a key role in neuroinflammation regulation by regulating the polarization state of astrocytes and the release of inflammatory factors, and may affect the integrity of the blood–brain barrier and a variety of pathologic injury processes. In view of the important role of LCN2 in CIRI, this article reviews the mechanism of LCN2, aiming to provide new ideas and methods for the treatment of ischemic stroke.